Young Mothers’ Fertility Decisions and Ideal Family Size in Peri-Urban Indonesia - Seri Aryati (Populasi, 2026)
This study addresses the growing demographic transition in peri-urban Indonesia, where changing socio-economic conditions increasingly shape fertility behaviour yet remain underexplored from women’s subjective perspectives. It examines how young mothers construct their perceptions of ideal family size and make fertility decisions in Depok Subdistrict, Sleman Regency, Special Region of Yogyakarta. Using a descriptive qualitative approach, the research involved married women aged 20–35 years with one or two children. Data were collected through in-depth interviews in Condongcatur and Maguwoharjo villages and analysed thematically.Findings indicate that most respondents perceive two children as the ideal family size, driven primarily by economic considerations, aspirations for quality childcare, and the need to balance reproductive and productive roles. Contextual variations arise from gender composition preferences and emotional motivations such as sibling companionship. Fertility decisions are influenced by household economic conditions, educational attainment, employment status, and the perceived function of family planning as a birth-spacing mechanism rather than a family-size determinant. Social pressure from extended families remains limited.This study contributes novel qualitative evidence on fertility norm internalisation in peri-urban contexts, highlighting how economic rationality increasingly replaces traditional pronatalist influences in shaping reproductive choices. It offers policy-relevant insights for context-sensitive family planning interventions.